Turning Up the Temperature on CRISPR: Increased Temperature Can Improve the Editing Efficiency of Wheat Using CRISPR/Cas9 - Milner, Matthew J.; Craze, Melanie; Hope, Matthew S.; Wallington, Emma J. (Frontiers in Plant Science, 2020)
The application of CRISPR/Cas9 technologies has transformed our ability to target and edit designated regions of a genome. It’s broad adaptability to any organism has led to countless advancements in our understanding of many biological processes. Many current tools are designed for simple plant systems such as diploid species, however efficient deployment in crop species requires a greater efficiency of editing as these often contain polyploid genomes. Here, we examined the role of temperature to understand if CRISPR/Cas9 editing efficiency can be improved in wheat. The recent finding that plant growth under higher temperatures could increase mutation rates was tested with Cas9 expressed from two different promoters in wheat. Increasing the temperature of the tissue culture or of the seed germination and early growth phase increases the frequency of mutation in wheat when the Cas9 enzyme is driven by the ZmUbi promoter but not OsActin. In contrast, Cas9 expression driven by the OsActin promoter did not increase the mutations detected in either transformed lines or during the transformation process itself. These results demonstrate that CRISPR/Cas9 editing efficiency can be significantly increased in a polyploid cereal species with a simple change in growth conditions to facilitate increased mutations for the creation of homozygous or null knock-outs.